The Flanders' interaction analysis categories (FIAC) as an instructional supervisory tool in Purisima School Tago, Surigao del Sur - Portillo, Fidelisa de Marie (Animo Repository, 1980)
This is a non-equivalent control group of a quasi-experimental type of study in Purisima School using interaction analysis as an instructional supervisory tool to find out the degree of difference existing between the verbal behaviors of teachers trained in IA and those who are untrained, as assessed particularly by the Flanders Interaction Categories technique. Specifically, this study aims to answer the following questions: 1) Measured by the Flanders Interaction Analysis Categories technique, what is the proportion in the amount of teacher talk (TT) in classes taught by teachers trained in IA and those who are untrained? 2) What is the difference in the response ratio (TRR) of teachers trained in IA and those who are untrained? 3) In guiding a more content-oriented class discussion, what is the ratio of questions (TQR) asked by teachers trained in IA and those who are untrained? 4) What is the proportion of the pupil talk (PT) in classes taught by teachers trained in IA and by those who are untrained? 5) How much initiative (PIR) is shown by pupils under the teachers trained in IA and under those who are untrained? 6) What is the indirect-to-direct (I/D) ratio of influence exerted by teachers trained in IA and by those who are untrained? The 1979-1980 teachers of Purisima School constitute the members of the experimental and control groups. Of the 13 school teachers, only 10 were taken for the study because of the small number of teachers who could be matched adequately. However, the members of the group were reduced to 4 pairs when one teacher left the school. The assignment of FIAC training was given at random to one group after the computed I/D ratio was found to be nearly equal. The main classes handled by the two groups were the brighter sections of the third and fourth years. There was a schedule of class observations for the teachers concerned. Each teacher was observed by the Principal and/or the researcher three times before and three times after the FIAC training. The class observations for each session lasted for 20 minutes with a five-minute time interval in coding the verbal interaction using the Flanders' technique which consists of 10 categories. Gain scores between the two groups were subjected to a t-test. This investigated the effectiveness of using the FIAC technique as an instructional supervisory tool to identify the teachers' verbal behaviors and improve them through training in FIAC. Based on the findings, the conclusions drawn were: 1) When the teacher learned to code with FIAC and interpreted displays from specimen of his own verbal behavior, he became more responsive to the students' ideas or opinions. 2) When the teachers were responsive to the students' ideas, they were more flexible and were able to elicit the students' participation. 3) When the teachers were unusually responsive and used students' ideas, they led the discussion with fewer questions or direction, and the students improved in initiative by introducing their own ideas or opinions into the class discussions especially when their ideas were recognized or praised. 4) In classes with above average TRR and PT, the teacher-pupil interaction produced positive attitudes and constructive influence. 5) The Flanders Interaction Analysis Categories technique used as a supervisory tool can help improve the verbal teaching behaviors through feedback system in a more objective, and non-threatening way.